SISTEM PEMBERKASAN SERTIFIKASI GURU BERBASIS WEB - Dadi Rosadi; Intan Kurniasih (Jurnal Computech & Bisnis (e-Journal), 2015)
The existence of this system helps in accelerating the delivery of information to participants of certification and the Public Service of Education at District and Province, in addition to this information system provides the facility to document the transaction certification participants can upload files lack appropriate certification requirements are then carried out the verification process by the Public Service of Education at District and Province through a SIP-PSG. The results of this study, of course, is expected to help speed processing of data is flawed document, however, the use of this system has not been tested for certified participants so the system cannot be measured the level of success. Keywords: System, Web Based  Abstrak Keberadaan sistem ini membantu dalam mempercepat penyampaian informasi kepada peserta sertifikasi dan Pelayanan Publik Pendidikan di Kabupaten dan Provinsi, di samping sistem informasi ini menyediakan fasilitas untuk mendokumentasikan peserta sertifikasi, transaksi dapat meng-upload file kekurangan persyaratan sertifikasi yang sesuai yang  kemudian dilakukan proses verifikasi oleh Pelayanan Publik Pendidikan di Kabupaten dan Propinsi melalui SIP - PSG. Hasil penelitian ini, diharapkan dapat membantu kecepatan pemrosesan data dalam pemerosesan dokumen data, namun penggunaan sistem ini belum diuji untuk peserta sertifikasi sehingga sistem tidak dapat diukur tingkat keberhasilannya. Kata Kunci: Sistem, Berbasis Web